2021
DOI: 10.1038/s41537-021-00150-7
|View full text |Cite
|
Sign up to set email alerts
|

Association of visual motor processing and social cognition in schizophrenia

Abstract: Patients with schizophrenia have difficulties in social cognitive domains including emotion recognition and mentalization, and in sensorimotor processing and learning. The relationship between social cognitive deficits and sensorimotor function in patients with schizophrenia remains largely unexplored. With the hypothesis that impaired visual motor processing may decelerate information processing and subsequently affects various domains of social cognition, we examined the association of nonverbal emotion reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 80 publications
0
1
0
Order By: Relevance
“…Bicluster (BiCs) 1, 2, 4, and 5 show significant connectivity differences mostly among visual (VS), subcortical (SC), and sensorimotor (SM). Neuroimaging research has identified these domains to be associated with schizophrenia dysfunction and social impairments [25]. Reduced connectivity strength (BiC 2) and opposite connectivity (BiC 5) between SM and VS are conceivably responsible for the obstruction in social cognition and mentalization [27, 25].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bicluster (BiCs) 1, 2, 4, and 5 show significant connectivity differences mostly among visual (VS), subcortical (SC), and sensorimotor (SM). Neuroimaging research has identified these domains to be associated with schizophrenia dysfunction and social impairments [25]. Reduced connectivity strength (BiC 2) and opposite connectivity (BiC 5) between SM and VS are conceivably responsible for the obstruction in social cognition and mentalization [27, 25].…”
Section: Resultsmentioning
confidence: 99%
“…Neuroimaging research has identified these domains to be associated with schizophrenia dysfunction and social impairments [25]. Reduced connectivity strength (BiC 2) and opposite connectivity (BiC 5) between SM and VS are conceivably responsible for the obstruction in social cognition and mentalization [27, 25]. The biclusters also depict significant group differences between schizophrenia (SZ) and the healthy control (HC) cohort.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Repetitive violence in patients with schizophrenia (vSZ) is generally associated with coexisting cognitive impairment, deficits in neurocognition (such as memory, motor function, and motor lapses in daily life, and perceptual-motor processing speed), impaired social cognitive function, and ineffective communication [12,13]. Neuro-and social cognitive deficits in schizophrenia are not only an enduring feature of the illness, but also a predictor of clinical and functional outcomes [14].…”
Section: Introductionmentioning
confidence: 99%